The Analysis of Discriminatory Discourses against African American in When They See Us Movie Series: A Critical Discourse Study - Feby Melina; Andi Muhammad Irawan (English Language and Literature, 2023)
This study aims to determine (1) the topic of discourse and (2) the discourse strategy of the utterances produced by whites in the When They See Us movie series as discriminatory actors to reveal how they voice their ideology when discriminating against blacks in their discourse. The researcher used qualitative methods because the data is in the form of written texts and also understands the meaning attached by a group to a social problem. In particular, the researcher analyzed the discourse presented in the When They See Us movie series which is transcribed into written discourses. This study focuses on how whites describe themselves positively and how whites portray blacks negatively in their discourse based on their beliefs. From the movie series that have been analyzed, the research found 83 data consisting of the presentation of positive-self and negative-other. By using the Van Dijk’s ideological square approach, the researcher found 10 discourse topics of blacks and 5 discourse topics of whites. In addition, there were 12 discriminatory discourse strategies used by whites to represent blacks negatively and 4 discourse strategies that whites used to represent themselves positively.